Introduction to Android-Based Numerical Learning at SD Muhammadiyah 2 Waru Sidoarjo (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Numeracy learning in SD Muhammadiyah 2 Waru Sidoarjo still uses conventional method, namely by using lectures and manual practice questions. In the current technological era, android-based learning is needed in accordance with the times so that learning numeracy feels more fun for students. In fact, playing games on gadgets will be more fun than learning at conventional schools. Therefore, the introduction of more modern numeracy media through android-based learning can increase student interest through indirect learning. According to the survey, as many as 50% of students at SD Muhammadiyah 2 Waru Sidoarjo do not like numeracy because many factors include the difficulty of understanding manual calculations. The purpose of this activity is to introduce numeracy learning that is more fun through android-based numeracy media. The method used in the introduction of android-based numeration media is a quantitative method by taking a sample of students at SD Muhamadiyah 2 Waru Sidoarjo as many as 15 students consisting of grades 1, 2, and 3. The introduction of android-based numeracy learning is done by providing knowledge to students and introducing Android-based numeracy applications. The results obtained from this dedication are that students know the android-baesd numeration application and students are more interests in learning numeracy which is more fun as well as games found on gadgets.